Gender Impact on Performance in Adaptive Learning Settings: Insights from a Four-Year University Study - Ademi Neslihan; Loshkovska Suzana (MDPI, 2025)
This study explores the role of gender in shaping learners’ outcomes in an adaptive learning environment. Despite the growing adoption of adaptive learning platforms in various educational settings, the literature on gender-related differences in engagement and achievement remains limited. Using quantitative analysis of performance and engagement data from learners, this study aims to shed light on how gender affects success and engagement in adaptive learning settings at the university level in formal education environments. The findings reveal significant differences in both achievement and engagement, emphasizing the importance of considering gender in adaptive course design. This study contains data from four years of the same course with different adaptive course settings and shows the impact of these settings on academic performance and engagement level based on gender.
Keywords: adaptive learning; higher education; learning analytics; gender; performance; engagement